Accommodating a vision of diversity in different school contexts: "Unity-in-Diversity" in Indonesia - Harjatanaya, TY (2020)
This thesis explores the ways in which schools accommodate the national vision of a multicultural society, specifically focusing on Indonesia’s national vision of “Bhinneka Tunggal Ika” (Unity-in-Diversity). Employing a multiple-case-study research approach, it examines the ways head teachers, teachers, students, and parents from six state and private schools with different mixes of student ethnicity and religiosity promote this national vision in terms of educational practice. The research considers the perspectives of education stakeholders on the meanings of Unity-in-Diversity and their responses in promoting Unity-in-Diversity in schools and classrooms in contemporary Indonesia, drawing data from observations, interviews, photos, and documentary analysis.